ABC-VEN ANALYSIS FOR OPTIMIZING CHRONIC DISEASE MEDICINE INVENTORY: A SCOPING REVIEW - Azharayesha Nurendra Deltaverona Mahardika; Muhammad Murtadho; Sutopo Patria Jati; Septo Pawelas Arso (International Archives of Medical Sciences and Public Health, 2026)
Chronic disease care requires stable medicine availability and efficient pharmaceutical spending. This scoping review mapped empirical evidence on the use of ABC-VEN/VED analysis for chronic disease medicine inventory optimization in health facilities. PubMed, ScienceDirect, Scopus, and Google Scholar were searched in July 2026 for full-text empirical studies published from 1 January 2021 to 30 June 2026. Screening followed PRISMA-ScR. After duplicate removal, 672 records were screened and 232 studies were included. The evidence showed that a small proportion of high-value and clinically important medicines accounted for most pharmaceutical expenditure. ABC-VEN/VED was used to support medicine planning, procurement prioritization, stock monitoring, stock-out reduction, overstock control, and waste prevention. Integrating ABC-VEN/VED into routine inventory policy may support rational pharmaceutical budgeting, improve medicine availability, and strengthen continuity of chronic disease treatment.